2023
DOI: 10.1111/sjop.12955
|View full text |Cite
|
Sign up to set email alerts
|

Examining generational differences as a moderator of extreme‐context perception and its impact on work alienation organizational outcomes: Implications for the workplace and remote work transformation

Ali B. Mahmoud,
Alexander Berman,
William Reisel
et al.

Abstract: There is no doubt that extreme contexts (e.g., war zones and pandemics) represent substantial disruptions that force many companies to rethink the way they do business. With so much of the workforce now working remotely and concerns about resulting work alienation, we must ask this question: How can this be translated into the generational divide in workplaces based in extreme contexts? Using COVID‐19 as an example trigger of extreme‐context experience, therefore, we investigate generation as a moderator of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Within this context, it is essential to acknowledge that individuals in Israel, as well as in similar regions, often possess a heightened perception of susceptibility to ambiguous or uncertain events. This perception has led to the formulation of deeply ingrained beliefs and institutions designed to shield against these uncertainties [ 23 ]. In light of this, policymakers must direct their efforts toward initiatives that extend beyond addressing immediate pandemic-related challenges and instead promote long-term resilience within society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, it is essential to acknowledge that individuals in Israel, as well as in similar regions, often possess a heightened perception of susceptibility to ambiguous or uncertain events. This perception has led to the formulation of deeply ingrained beliefs and institutions designed to shield against these uncertainties [ 23 ]. In light of this, policymakers must direct their efforts toward initiatives that extend beyond addressing immediate pandemic-related challenges and instead promote long-term resilience within society.…”
Section: Discussionmentioning
confidence: 99%
“…Age is an additional factor associated with COVID-19 outcomes, as both the elderly (older than 60) and young adults (aged [18][19][20][21][22][23][24][25][26][27][28][29][30] have demonstrated the highest levels of psychological distress, although results vary across studies [19][20][21][22]. Notably, a study conducted within Middle Eastern Arab nations revealed that both Generation Y and Generation Z individuals exhibited heightened anxiety in response to extreme-context perceptions, subsequently leading to increased job insecurity due to feelings of alienation, in contrast to Generation X respondents [23].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Firstly, it is important to acknowledge that other demographic variables may also have moderating effects on the relationship between value-based leadership, growth mindset, and intrinsic work motivation among Chinese lecturers. For example, recent studies by [ 103 ] have shown that gender can play a significant role in influencing cognitive and behavioral outcomes. Therefore, future research could explore the potential influence of gender as a moderating variable in this context.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Therefore, future research could explore the potential influence of gender as a moderating variable in this context. Furthermore, considering the impact of individuals’ self-efficacy on managerial behaviors in higher education, as highlighted by [ 103 ], could provide valuable insights into the dynamics between value-based leadership, growth mindset, and intrinsic work motivation among lecturers. Incorporating self-efficacy as a determinant in future studies could enhance our understanding of the complex interplay of factors affecting lecturers’ motivation.…”
Section: Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation